Notary's Responsibility in Carrying Out Official Secrecy Regarding the Contents of Deeds in Blora Regency - Azizah, Siti Nurul (Sultan Agung Notary Law Review, 2024)
One of the very noble legal professions (officium nobile) is the Notary profession, it is said so because of the work done by a Notary. Notaries have the authority to make deeds which are regulated in Article 15 paragraph (1), (2) and (3) UUJN. Notaries need the principle of caution in carrying out their duties, because if there is an error or negligence from the Notary in carrying out his position, it can cause legal problems for the Notary in the future. Notaries in carrying out their positions are obliged to maintain the confidentiality of all matters concerning deeds and other letters that have been made, this is regulated in Article 16 paragraph (1) letter f regarding the obligation to deny. This research was written using an empirical research method and using a qualitative approach, studied with analytical descriptive research specifications. The results of this study are that the Notary's responsibility is stated in Article 65 UUJN which explains that he is responsible for every deed he makes. The responsibility held by a notary adheres to the principle of liability based on fault of liability. The responsibility of a notary arises if there is an error made in carrying out his/her duties and the error causes a loss to the person requesting the notary's services. If the notary makes a mistake, he/she may be subject to civil, criminal and administrative sanctions. In order for a notary to be able to provide information in court, he must have the approval of the Notary Supervisory Board. This is regulated in Article 66 of the 2014 UUJN.